National Household Survey on Drug Abuse, 1979 ([Verlag nicht ermittelbar], 1998)
This series measures the prevalence and correlates of drug use in the United States. The surveys are designed to provide quarterly, as well as annual, estimates. Information is provided on the use of illicit drugs, alcohol, tobacco, and nonmedical use of prescription drugs among members of United States households aged 12 and older. Questions include age at first use, as well as lifetime, annual, and past-month usage for the following drug classes: cannabis, cocaine, hallucinogens, heroin, inhalants, alcohol, tobacco, nonmedical use of prescription drugs including psychotherapeutics, and polysubstance use. Respondents were also asked about their knowledge of drugs, perceptions of the risks involved, population movement, and sequencing of drug use. Fifty-seven percent of respondents were asked specific questions about their perceptions of the consequences of marijuana and alcohol use. The other 43 percent were asked about heroin use among friends. Demographic data include gender, race, age, ethnicity, marital status, educational level, job status, income level, and household composition.